(untitled) (International Journal of Engineering Management Science, 2022)
This paper investigates a novel PWM scheme for two phase interleaved boost converter with voltage multiplier for fuel cell power system by combining Alternating Phase Shift (APS) control and traditional interleaving PWM control. The APS control is used to reduce the voltage stress on switches in light load while the traditional interleaving control is used to keep better performance in heavy load. The boundary condition for swapping between APS and traditional interleaving PWM control is derived. Based on the above analysis, a full power range control combining APS and traditional interleaving control is proposed. Loss breakdown analysis is also given to explore the efficiency of the converter. Finally, it is verified by experimental results. Also, the reverse recovery problem of all diodes is mitigated and zero current-switching (ZCS) turn-on operation of the main switches is established as well. In addition, the passive clamp circuits are employed to suppress the voltage spikes across the main switches during turn-off instants. The operating principles and steady-state analysis of the proposed converter in continuous condition mode are explained. Finally, the simulation and experimental results of prototype 25–400 V circuit with 200 W output power are provided to verify the performance of presented topolog